Antihyperalgesic effects of dexmedetomidine on high-dose remifentanil-induced hyperalgesia - Cheol Lee; Yeon-Dong Kim; Ji-Na Kim (Korean Journal of Anesthesiology, 2013)
BackgroundDexmedetomidine is a highly selective α2 adrenergic agonist that has been shown to decrease the intensity of opioid-induced hyperalgesia (OIH). We aimed to investigate the antihyperalgesic effects of dexmedetomidine on high-dose remifentanil-induced hyperalgesia.MethodsNinety American Society of Anesthesiologists physical status I-II patients undergoing laparoscopically assisted vaginal hysterectomy (LAVH) were randomly assigned to one of the following three groups, each of which received either dexmedetomidine (an initial dose of 1.0 µg/kg for 10 min, followed by a continuous infusion of 0.7 µg/kg/hr) or placebo saline 15 min before the induction of anesthesia and intraoperative remifentanil infusion: group C received a placebo and 0.05 µg/kg/min remifentanil; group RH received a placebo and 0.3 µg/kg/min remifentanil; and group DRH received dexmedetomidine and 0.3 µg/kg/min remifentanil.ResultsThe mechanical hyperalgesia threshold 24 hr after surgery was significantly lower in group RH than in the other two groups. Postoperative pain intensity using visual analog scale (VAS) and cumulative volume of a patient-controlled analgesia (PCA) containing morphine over 24 hr were significantly greater in group RH than in group DRH. The time to the first postoperative analgesic requirement was significantly shorter in group RH than in the other two groups. The desflurane requirement was significantly greater in group C than in the other groups. The frequency of hypotension and bradycardia was significantly higher, but shivering and postoperative nausea and vomiting were significantly lower in group DRH than in the other two groups.ConclusionsHigh-doses of remifentanil induced hyperalgesia, which presented a decreased mechanical hyperalgesia threshold, enhanced pain intensity, a shorter time to first postoperative analgesic requirement, and greater morphine consumption, but dexmedetomidine efficiently alleviated those symptoms. Dexmedetomidine may be a novel and effective treatment option for preventing or attenuating OIH.